THE MAIN APPROACHES TO GROUPING SETTLEMENT HYDROECOSYSTEMS OF CHERKASY REGION - Шутак, Карина; Киселев, Юрий (SWorldJournal, 2020)
The essence of the notion “settlement hydroecosystem” is described in the publication. Examples of groups of settlement hydroecosystems shaped on the ground of the basin and ekistics approaches are given at the materials taken from Cherkasy region (Ukrain